Assessing Digital Competence Among Pre-Service English Language Teachers: Strengths and Weakenesses - Sri Sumarni; Ifan Iskandar; Imam Santosa (Journal of English Education and Teaching, 2023)
This study aimed to examine the digital competence of 102 pre-service English language teachers and identified areas of strength and weakness. A questionnaire aligned with the European Framework for Educators' Digital Competence (DigCompEdu) was used to assess self-perceived competence in various digital areas. The findings revealed strengths in organizational communication, professional collaboration, managing and sharing digital resources, guidance, collaborative and self-regulated learning, accessibility and inclusion, and digital content creation. However, reflective practice and analyzing evidence were identified as areas of relative weakness. The study highlighted the need for targeted training programs and curriculum enhancements to address these gaps. Enhancing the digital competence of pre-service teachers is crucial for effective integration of technology in language instruction. By addressing strengths and weaknesses, the study emphasized the importance of comprehensive digital education programs that go beyond assuming digital natives possess advanced skills. Improving digital competence among pre-service teachers can enhance the quality of language education and provide better learning experiences for students.